2021
DOI: 10.17159/2413-3221/2021/v49n3a12823
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic factors affecting home gardens as a livelihood strategy in rural areas of the Eastern Cape province, South Africa

Abstract: Home gardens have been identified as one of the possible ways of producing food and offer great solutions to some of the issues surrounding poverty alleviation and improving food security in rural areas. However, home gardens' potential as a living strategy has not been recognized and affected by many factors. Therefore, the study examines socio-economic factors influencing home gardens as a living strategy in rural areas of the Eastern Cape Province. The study was conducted in the Eastern Cape Province rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
2
7
1
Order By: Relevance
“…The study results showed that the majority (69%) of the farming households were married and this played a huge role in decision-making, as married farmers thought about the well-being of their households, as well as assisted in the provision of family labour. These results were in line with the findings of [44]. Household size was employed as a proxy for measuring household labour with the study results indicating that the mean household size was five persons per household, which played an important role in tree planting.…”
Section: Demographic Features Of Farmerssupporting
confidence: 90%
See 1 more Smart Citation
“…The study results showed that the majority (69%) of the farming households were married and this played a huge role in decision-making, as married farmers thought about the well-being of their households, as well as assisted in the provision of family labour. These results were in line with the findings of [44]. Household size was employed as a proxy for measuring household labour with the study results indicating that the mean household size was five persons per household, which played an important role in tree planting.…”
Section: Demographic Features Of Farmerssupporting
confidence: 90%
“…Comparatively, to discriminant examination, the Logit regression model is more applicable to a larger range of exploration conditions. Due to its superior comparative mathematical simplicity, this model was adopted over the Probit model [43,44]. The ability of this model to more effectively address the primary research objectives as well as the characteristics of the data and sample (association between variables, slope indicating how the log odds ratio is in favour of adoption urban tree planting) led to its selection.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…The average number of years spent in school by smallholder farmers was 12 years, which is equivalent to secondary education in South Africa. These farmers were in line with Mujuru et al (2022), Sigigaba et al (2021) and Mdiya and Mdoda (2021) that smallholder farmers in the Eastern Cape Province are literate, which enables them the opportunity to access new innovative agricultural practices, market information and take well-informed decision regarding the farm as they are knowledgeable. This played an important role in smallholder irrigation farming as they have all the necessary skills and knowledge to operate farms and machinery to enhance productivity.…”
Section: Data and Sources Of Datamentioning
confidence: 88%
“…For instance, Dissanayake and Manawadu (2019) found that factors such as basic knowledge in crop production practices, ability to obtain quality seeds and planting materials were among factors affecting the backyard gardeners' food security status. Mdiya and Mdoda (2021) found that location, years spent in school, total household income, land ownership, age, off-farm income, and family size were among other factors affecting backyard gardeners' food security status. Research by Mcata and Obi (2015) as well as Mokone (2016) conclude that household income, engagement in non-farm activities, years of experience in gardening, and the proportion of produce consumed impacted the food security status of backyard gardeners.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Some insights on household indicators that can explain the food security status of households practising backyard gardening in South Africa is given in various studies that include Mcata and Obi (2015); Dissanayake and Manawadu (2019); Mdiya and Mdoda (2021); Mokone (2016). For instance, Dissanayake and Manawadu (2019) found that factors such as basic knowledge in crop production practices, ability to obtain quality seeds and planting materials were among factors affecting the backyard gardeners' food security status.…”
Section: Brief Literature Reviewmentioning
confidence: 99%